Part-Time and Casual Work in Retail Trade: Stress and other Factors Affecting the Workplace - Zeytinoglu, Isik; Lillevik, Waheeda; Seaton, Bianca; Moruz, Josefina (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2004)
The purpose of this article is to examine the effects of working conditions in part-time and casual work on worker stress and the consequences for their workplaces. Data were collected through interviews with occupational health and safety representatives, and focus groups and interviews with workers in retail trade. Results show that job insecurity, short- and split-shifts, unpredictability of hours, low wages and benefits in part-time and casual jobs in retail sector, and the need to juggle multiple jobs to earn a living wage contribute to stress and workplace problems of absenteeism, high turnover and workplace conflicts. Gendered work environments and work-personal life conflicts also contribute to stress affecting the workplace. Equitable treatment of part-time and casual workers, treating workers with respect and dignity, and creating a gender-neutral, safe and healthy work environment can help decrease stress, and in turn, can lead to positive workplace outcomes for retail workers.